2007
DOI: 10.1111/j.1365-313x.2007.03303.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput quantitative luminescence assay of the growth in planta of Pseudomonas syringae chromosomally tagged with Photorhabdus luminescens luxCDABE

Abstract: SummaryBioluminescent strains of the Arabidopsis thaliana pathogens Pseudomonas syringae pathovar (pv.) tomato and pv. maculicola were made by insertion of the luxCDABE operon from Photorhabdus luminescens into the P. syringae chromosome under the control of a constitutive promoter. Stable integration of luxCDABE did not affect bacterial fitness, growth in planta or disease outcome. Luminescence accurately and reliably reported bacterial growth in infected Arabidopsis leaves both with a fixed inoculum followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(167 citation statements)
references
References 20 publications
2
163
1
1
Order By: Relevance
“…S2B). Similar results were obtained after inoculation with a bioluminescent strain of PstDC3000 (PstDC3000-lux; Fan et al, 2008): Whereas P 1 wild-type plants developed less bioluminescence and fewer disease symptoms than C 1 wild-type plants, no such differences were observed between P 1 and C 1 progeny from the npr1-1 mutant (Supplemental Fig. S4).…”
Section: Plants Exposed To Fitness-reducing Levels Of Disease Producesupporting
confidence: 71%
See 1 more Smart Citation
“…S2B). Similar results were obtained after inoculation with a bioluminescent strain of PstDC3000 (PstDC3000-lux; Fan et al, 2008): Whereas P 1 wild-type plants developed less bioluminescence and fewer disease symptoms than C 1 wild-type plants, no such differences were observed between P 1 and C 1 progeny from the npr1-1 mutant (Supplemental Fig. S4).…”
Section: Plants Exposed To Fitness-reducing Levels Of Disease Producesupporting
confidence: 71%
“…PstDC3000 assays were performed with a bioluminescent luxCDABEtagged strain (PstDC3000-lux; Fan et al, 2008). Five-week-old plants were inoculated by dipping the leaves in a bacterial suspension containing 10 8 colony-forming units/mL in 10 mM MgSO 4 and 0.01% (v/v) Silwet L-77.…”
Section: Basal Resistance Assaysmentioning
confidence: 99%
“…This facilitates in planta quantification of bioluminescent Pst-DC3000-Lux bacteria due to the presence of the LuxCDABE operon from Photorhabdus luminescens inserted into the P. syringae chromosome (Fan et al, 2008). During the non-SAR induced treatment (mock/PstDC3000- Fig.…”
Section: Figure 2 H Arabidopsidis Conidiophores Present In Various Amentioning
confidence: 99%
“…Growth of Pst-DC3000-Lux was determined quantitatively 48 h after the secondary challenge using 8mm leaf discs excised from Pst-DC3000-Lux-infiltrated leaves as described by Fan et al (2008). A total of 12 plants were used for each time point.…”
Section: Infection With P Syringaementioning
confidence: 99%
“…A collection of 8,000 activation tagged T1 plants in the NahG background were screened by hand-infiltration with virulent P. syringae pv maculicola ES4326 (Psm) chromosomally tagged with luxCDABE (Fan et al, 2008). While no mutant was found that enhanced basal resistance in the absence of SA, a mutant with increased disease severity was identified.…”
Section: Cds2-1d Is a Dominant Mutation Conferring Enhanced Disease Smentioning
confidence: 99%